Slurs: Semantic Content, Expressive Content and Social Generics - Federico Cella (Rosenberg & Sellier, 2017)
Slurs are offensive expressions targeting individuals on the basis of their membership to certain social groups. Some authors have argued that the offensiveness of slurs is related to the semantic encoding of stereotypes in their meaning. As noticed by Robin Jeshion (2011, 2013a, 2013b), the stereotypical strategies do not seem to provide a satisfactory analysis of slurs’ functional traits. Herein, I propose to modify her view by making a distinction between two offensive dimensions of slurs: a negative expressive component encoded in the semantic content and directed toward a certain group of individuals, and the social generics related to that group conveyed as conversational implicatures.